A Systematic Analysis of Telemedicine Behavior, Compliance and Cyber Resilience In Indonesia - Jaya, Ade Indra; Kadarisman, Sumeidi; Agusiady, Raden Ricky (Amkop Management Accounting Review (AMAR), 2025)
Indonesia’s digital health push has fostered an integrated telemedicine ecosystem centered on SATUSEHAT Mobile and major private platforms, intensifying cross-system clinical data exchange. This raises the salience of three dimensions: behavior (human factors), compliance (regulatory/standards alignment), and cyber resilience (prevent, respond, and recover). This study maps the evidence on these dimensions in Indonesia’s telemedicine context and develops a maturity evaluation model with baseline operational practices. We conducted a Systematic Literature Review guided by PRISMA, covering publications from 2020 to 2025 in major scholarly databases under inclusion criteria specific to Indonesian telemedicine. Eligible studies were extracted and analyzed qualitatively using NVivo, with open axial selective coding, to produce a thematic synthesis and a concept map across the three focal dimensions. The synthesis yields four theme clusters: (1) behavior & security literacy (credential hygiene, social engineering awareness, BYOD/remote access); (2) audit & operational compliance (logging/audit trails, breach reporting, adoption of standards/certifications); and (3) incident response & resilience (runbooks, backup/restore, failover, BCP/DRP testing). Key gaps include consent traceability across FHIR-based interoperability flows, end-to-end resilience indicators (e.g., integration MTTR, standardized failover tests), and comparative cross-platform assessments. Outputs comprise a behavior→compliance→resilience conceptual model, a maturity evaluation framework, and non-policy baseline operational practices.